2010
DOI: 10.1152/physiolgenomics.00042.2010
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific genetic dissection of diabetes in a rodent model identifies Ica1 and Ndufa4 as major candidate genes

Abstract: The aim of the study was to initiate a sex-specific investigation of the molecular basis of diabetes, using a genomic approach in the Cohen Diabetic rat model of diet-induced Type 2 diabetes. We used an F2 population resulting from a cross between Cohen Diabetic susceptible (CDs) and resistant (CDr) and consisting of 132 males and 159 females to detect relevant QTLs by linkage and cosegregation analyses. To confirm the functional relevance of the QTL, we applied the “chromosome substitution” strategy. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…In our previous studies, focusing primarily on the initiation phase of diabetes, we detected after 1 month of DD one major genomic locus on RNO4, which failed, however, to explain the full genetic variation of the diabetic phenotype at that time point (3,2). In the current study, we confirmed the same genomic locus on RNO4 but established, based on a high LOD score at 1 month that gradually diminished after 2.5 and Figure 5.…”
Section: Three Loci Effectsupporting
confidence: 73%
See 4 more Smart Citations
“…In our previous studies, focusing primarily on the initiation phase of diabetes, we detected after 1 month of DD one major genomic locus on RNO4, which failed, however, to explain the full genetic variation of the diabetic phenotype at that time point (3,2). In the current study, we confirmed the same genomic locus on RNO4 but established, based on a high LOD score at 1 month that gradually diminished after 2.5 and Figure 5.…”
Section: Three Loci Effectsupporting
confidence: 73%
“…We performed cosegregation analysis at each quantitative trait locus (genomic locus) detected by linkage analysis, as previously described (3,2). In brief, we compared by ANOVA the phenotype in F2 between those with the various phases of the development of diabetes.…”
Section: Candidate Genesmentioning
confidence: 99%
See 3 more Smart Citations